Developmental stage-dependent regulation of spine formation by calcium-calmodulin-dependent protein kinase IIα and Rap1. Issue 1 (December 2017) - Cornelia Koeberle, Solveigh; Tanaka, Shinji; Kuriu, Toshihiko; Iwasaki, Hirohide; Koeberle, Andreas; Schulz, Alexander; Helbing, Dario-Lucas; Yamagata, Yoko; Morrison, Helen; Okabe, Shigeo
Abstract The roles of calcium-calmodulin-dependent protein kinase II-alpha (CaMKIIα) in the expression of long-term synaptic plasticity in the adult brain have been extensively studied. However, how increased CaMKIIα activity controls the maturation of neuronal circuits remains incompletely understood. Herein, we show that pyramidal neurons without CaMKIIα activity upregulate the rate of spine addition, resulting in elevated spine density. Genetic elimination of CaMKIIα activity specifically eliminated the observed maturation-dependent suppression of spine formation. Enhanced spine formation was associated with the stabilization of actin in the spine and could be reversed by increasing the activity of the small GTPase Rap1. CaMKIIα activity was critical in the phosphorylation of synaptic Ras GTPase-activating protein (synGAP), the dispersion of synGAP from postsynaptic sites, and the activation of postsynaptic Rap1. CaMKIIα is already known to be essential in learning and memory, but our findings suggest that CaMKIIα plays an important activity-dependent role in restricting spine density during postnatal development.